Placental Growth Factor Contributes to Liver Inflammation, Angiogenesis, Fibrosis in Mice by Promoting Hepatic Macrophage Recruitment and Activation - Li, Xi; Jin, Qianwen; Yao, Qunyan; Zhou, Yi; Zou, Yanting; Li, Zheng; Zhang, Shuncai; Tu, Chuantao (Frontiers in Immunology, 2017)
Placental growth factor (PlGF), a member of the vascular endothelial growth factor (VEGF) family, mediates wound healing and inflammatory responses, exerting an effect on liver fibrosis and angiogenesis; however, the precise mechanism remains unclear. The aims of this study are to identify the role of PlGF in liver inflammation and fibrosis induced by bile duct ligation (BDL) in mice, and to reveal the underlying molecular mechanism. PlGF small interfering RNA (siRNA) or non-targeting control siRNA was injected by tail vein starting two days after BDL. Liver inflammation, fibrosis, angiogenesis, macrophage infiltration and hepatic stellate cells (HSCs) activation were examined. Our results showed that PlGF was highly expressed in fibrotic livers and mainly distributed in activated HSCs and macrophages. Furthermore, PlGF silencing strongly reduced the severity of liver inflammation and fibrosis, and inhibited the activation of HSCs. Remarkably, PlGF silencing also attenuated BDL-induced hepatic angiogenesis, as evidenced by attenuated liver endothelial cell markers CD31 and vWF immunostaining and genes or protein expression. Interestingly, these pathological ameliorations by PlGF silencing were due to a marked reduction in the numbers of intrahepatic F4/80+, CD68+, and Ly6C+ cell populations, which were reflected by a lower expression of these macrophage marker molecules in fibrotic livers. Additionally, knockdown of PlGF by siRNA inhibited macrophages activation and substantially suppressed the expression of proinflammatory cytokines and chemokines in fibrotic livers. Mechanistically, evaluation of cultured Raw 264.7 cells revealed that VEGF receptor 1 (VEGFR1) mainly involved in mediating the role of PlGF in macrophages recruitment and activation, since using VEGFR1 neutralizing antibody blocking PlGF/VEGFR1 signaling axis significantly inhibited macrophages migration and inflammatory responses. Together, these findings indicate that PlGF plays an important role in liver inflammation, angiogenesis and fibrosis by promoting hepatic macrophage recruitment and activation, and suggest that blockage of PlGF could be a promising novel therapy for chronic fibrotic liver diseases.